Aspectos epidemiológicos da Leishmaniose Visceral Humana no Brasil e estados e cidades gêmeas do país, com enfoque no estado e na cidade gêmea com maior número de casos - Oliveira, Lara Camila de (2021)
Human Visceral Leishmaniasis (HVL), transmitted by vectors, with the dog being the main reservoir, has been of great importance for public health and with wide geographical distribution, especially in the border region, where vectors and dogs move freely. Objective: To verify the number of notified cases of HVL in Brazil and in the country's twin states and cities, focusing on the state and in the twin city with the highest number of cases, as well as investigating the clinical, demographic, social and epidemiological aspects in the period investigated. Material and methods: This is a cross sectional, observational, descriptive and retrospective study, with a quantitative approach, developed from secondary HVL data from the period 2010 to 2019. The data were obtained through the public domain website of the Informatics Department of the Unified Health System. The data were presented in Absolute Frequency and Relative Frequency. HVL rates per 100,000 inhabitants were calculated, referring to the state and twin city with the highest number of cases. The data for each variable were analyzed using the Mann-Whitney test, with a significance level of 5%, using the Minitab 18 program. Results: In Brazil, 35,886 cases of HVL were reported in the studied period, of these 2834 cases in international border states, 148 in twin cities. The border state and municipality with the highest number of cases was Mato Grosso do Sul (MS) (1834 cases) and Corumbá (94 cases). In MS there was a greater concentration of the number of cases in the years 2010 to 2013 with a subsequent reduction. The municipality of Corumbá had the highest number of cases in the years 2014 and 2017 to 2019, with 91 being indigenous to the municipality of residence and the average annual detection rate was 8.3 cases/100,000 inhabitants. The disease was more frequent in males, corresponding to 64.0% of patients in the MS and 65.0% in Corumbá (p <0.05), with the majority self-declared to be brown (p = 0.0001), representing 52.9% and 76.7% of patients. As for schooling, in MS and Corumbá the highest frequency of cases of LVH was in the group with up to 8 years of study 34.0% and 29.7% (p = 0.0001).The age range ranged from children under one year of age (n = 141) to those over 80 years of age (n = 41), in MS and, among children under one year of age (n = 18) to 79 years (n = 4), in Corumbá, with 25.2% and 42.5% of patients up to four years of age and 48.1% and 33.9 between 20 and 59 years in the MS and in Corumbá (p <0.05). Of the cases of death due to HVL, they were reported in the state of MS 7.4% deaths and 16.0% deaths in the municipality of Corumbá. Most cases occurred in the urban area (p = 0.0001) Conclusion: A high number of notified cases of VHL in Brazil during the study period is concluded, distributed in 10 states with international borders, with eight twin cities standing out. Among the border states and twin cities, MS and Corumbá were the most affected by the disease, and the disease was frequent in males, in children under four and young adults aged 20 to 59 years, in people of mixed color and up to 8 years of study. Most cases occurred in urban areas and progressed to cure.